2017
DOI: 10.1038/s41598-017-02076-6
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome sequence of tung tree (Vernicia fordii): Organization and phylogenetic relationships with other angiosperms

Abstract: Tung tree (Vernicia fordii) is an economically important tree widely cultivated for industrial oil production in China. To better understand the molecular basis of tung tree chloroplasts, we sequenced and characterized its genome using PacBio RS II sequencing platforms. The chloroplast genome was sequenced with 161,528 bp in length, composed with one pair of inverted repeats (IRs) of 26,819 bp, which were separated by one small single copy (SSC; 18,758 bp) and one large single copy (LSC; 89,132 bp). The genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 60 publications
5
47
0
Order By: Relevance
“…The GC content of these sequenced genomes was consistent with a previously reported genome from this genus [37,38]. The number of repeats, including forward, tandem, and palindromic repeats, were studied in the chloroplast genomes sequenced and compared, and were found in a larger amount than in the previously reported cp genome of V. fordii (49 repeats) [32]. Among these repeats, tandem repeats were found several times more than palindromic and forward repeats, which are consistent with the Teucrium and Commiphora species [30,31], as well as S. miltiorrhiza [39], as previously reported.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The GC content of these sequenced genomes was consistent with a previously reported genome from this genus [37,38]. The number of repeats, including forward, tandem, and palindromic repeats, were studied in the chloroplast genomes sequenced and compared, and were found in a larger amount than in the previously reported cp genome of V. fordii (49 repeats) [32]. Among these repeats, tandem repeats were found several times more than palindromic and forward repeats, which are consistent with the Teucrium and Commiphora species [30,31], as well as S. miltiorrhiza [39], as previously reported.…”
Section: Discussionsupporting
confidence: 85%
“…SSRs (simple sequence repeats) are repeats that play an important role in genome stabilization and rearrangement of genome sequences, and these SSRs make the cp genome favorable because of its use as a molecular maker and phylogenetic analysis [40,41]. In our study 101 and 119 total SSRs were found in E. larica and E. smithii respectively, which is higher than the Euphorbiaceae family members [32]. However, it is similar to the previously reported B. sacra cp genome [42].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The trnH-psbA, trnK-rbcL, trnG-psbZ, psbD-trnT-trnE, petN-trnC, trnG-trnS, trnR-trnG-trnS, ndhI-ndhG, trnL-rpl32 loci and petD, rpl16, ndhA introns were most divergent regions, which were located in the intergenic spacers (IGSs) and introns, respectively. The boundary of IR regions indicated hypervariable regions with many nucleotide changes in chloroplast genomes of closely related species[43], simultaneously, the IR border expansion/contraction was considered as an evolutionary event[36]. In this study, we compared genes on the boundaries of the junction sites of the Psoralea corylifolia with other three species of Glycine ( Glycine max, Glycine gracilis, Glycine soja ) (Fig 2).…”
Section: Resultsmentioning
confidence: 99%